f(t)=3t-1

Simple and best practice solution for f(t)=3t-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(t)=3t-1 equation:


Simplifying
f(t) = 3t + -1

Multiply f * t
ft = 3t + -1

Reorder the terms:
ft = -1 + 3t

Solving
ft = -1 + 3t

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 't'.
f = -1t-1 + 3

Simplifying
f = -1t-1 + 3

Reorder the terms:
f = 3 + -1t-1

See similar equations:

| w=1000+-550t | | (18x-8)2=4x+16 | | 6x^2-x-37=0 | | 4x^2-14x+116=y | | lnx=(x+6)-ln(x-4) | | w=-2750+1100 | | w=-275+1100 | | Y=5x^2+3x-2 | | w^2+3w=54 | | 6d+12d=10d+35 | | Y=2x^2+17x+8 | | -13p=-3 | | Y=4x^2+11x-20 | | 4x+32=60 | | -15p=-3 | | 2x-1=9*x-6 | | Y=3x^2-14x-5 | | 14+(-80)= | | Y=x^2-144 | | 2.25-3x+x^2=18 | | 12x+11y=-77 | | 6a+9b=21 | | 3y=18x+24 | | 8x-2=3x-11 | | -3x+2.25+x^2=20.25 | | 2a+2b=10 | | 8x-2=3x+11 | | 2j-6-.5j=-12 | | 3(w+2)-(12-w)= | | 7e^7x=1820 | | m-(-4.7)=2.2 | | 20p=146 |

Equations solver categories